Joint and segmental mechanics differ between cutting maneuvers in skilled athletes - Havens, K. L.; Sigward, S. M. (Gait and Posture, 2015)
Cutting is necessary for participation in multidirectional sports but is also associated with non-contact ACL injury. Whole body demands of deceleration and redirection increase with greater cut angles. However, it is not known how these demands relate to differences in joint and segmental mechanics. Understanding the relationship between whole body and joint mechanics necessary for cutting and those related to risk for injury is important for the development of injury prevention training programs. The purpose of this study is to determine how joint and segmental mechanics change to meet increasing deceleration and redirection demands during cutting. Lower limb and trunk kinematics and kinetics were evaluated during the execution of two sidestep cutting maneuvers (to 45 and 90 degrees) in twenty-five healthy soccer players. A two-way multivariate analysis of covariance (MANCOVA) determined that differences existed between task directions but not sexes when considering all dependent variables and covarying for approach velocity (a = 0.05). Post hoc analyses revealed that the larger deceleration and redirection demands of the 90-degree cut did not translate into larger angles, moments and power across all lower extremity joints. In the sagittal plane, the knee appeared to primarily accommodate the greater deceleration demands of the sharper cut. These data further suggest that the hip may play a different role during cutting to smaller and larger angles and also illustrate a pattern of engagement in the sagittal and frontal planes that has not been described previously.